Comparison of two methods for calculating 3-dimensional ball spin, and its application to soccer kicking - Shorter, K.; Smith, N. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The aim of this study was to select an appropriate computational method for determining both spin axis direction, and spin rate during soccer ball flight. Calculation methods of Cross-Product (CP) and Singular Value Decomposition (SVD) were compared on a stationary spinning ball under laboratory conditions, using data collected from 10 Vicon MX cameras tracking 5mm hemispherical ball markers at 500Hz. When the ball was spun at 371 ± 15 RPM, spin axis orientation appeared close to `real` values, yet CP showed greater error in RPM estimation. Comparison of the methods during a kick showed no significant difference for spin rate calculation, yet CP underestimated the x and y spin axes, and overestimated spin around the z axis. It was proposed that SVD is used in future to estimate ball spin parameters, especially during kicking where marker occlusion may be more prevalent.